Parental warmth may not always be beneficial: High parental warmth impairs victimized adolescents' academic achievement via elevated school burnout. (June 2022) - Li, Caina; Tan, Xulan; Zhao, Qingling; Ren, Ping
Although research has documented the adverse effect of peer victimization on academic achievement, little is known about the underlying mechanism. This three-wave longitudinal study attempts to examine whether school burnout would explain the influence of peer victimization on academic achievement and whether this undesirable effect would be conditional on parental warmth using a sample of 706 Chinese adolescents (54.77% boys; M age = 12.72 years, SD = 0.40 at baseline). Both self-reported and peer-nominated victimization, school burnout, and parental warmth were assessed at baseline, and school burnout was measured 1 year later. Their academic achievement was collected from school records at baseline and 2 years later. The results revealed that self-reported (rather than peer-nominated) victimization at baseline impaired students' academic achievement 2 years later through increasing their school burnout. Interestingly, higher parental warmth aggravated, rather than alleviated this indirect effect. These findings support the Reverse Stress-Buffering Model and the Ecological Systems Theory highlighting the importance of considering multiple interpersonal relationships simultaneously to heighten adolescent academic performance.